Membangun Semangat Belajar Anak di Panti Asuhan Cinta Kasih Medan - Elviana Safitri; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Education is one of the crucial components of achieving prosperity. Education can support the quality of human resources, which will undoubtedly impact the progress of a nation. This it is essential to grow and improve children's enthusiasm for learning from an early age. Various efforts were made to encourage children's learning spirit, including the children at the Cinta Kasih Orphanage in Medan. Most children there prefer to play and have less enthusiasm for school, let alone an interest in learning, especially for those under ten years old. Through Practicum 1 activity held from March to May 2022, the author carried out a mini project for one of the children at the Cinta Kasih Orphanage in Medan. This activity is carried out using the casework method with general stages, including Engagement Intake Contract, Assessment, Planning, Intervention, Monitoring and Evaluation, and ends with Termination. The tools used in the assessment are ecomap tools that help find the sources of problems and a support system to overcome the problems experienced by clients. After going through the process using these stages and tools, the goal of growing and increasing the enthusiasm for children's learning in the orphanage was proven to be achieved. Of course, this will significantly affect the development of the client. Clients are motivated to continue learning at schools and orphanages with fun methods.